2005
DOI: 10.1242/jcs.02675
|View full text |Cite
|
Sign up to set email alerts
|

The mAKAP complex participates in the induction of cardiac myocyte hypertrophy by adrenergic receptor signaling

Abstract: Maladaptive cardiac hypertrophy can progress to congestive heart failure, a leading cause of morbidity and mortality in the United States. A better understanding of the intracellular signal transduction network that controls myocyte cell growth may suggest new therapeutic directions. mAKAP is a scaffold protein that has recently been shown to coordinate signal transduction enzymes important for cytokine-induced cardiac hypertrophy. We now extend this observation and show mAKAP is important for adrenergic-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
161
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(166 citation statements)
references
References 32 publications
3
161
0
2
Order By: Relevance
“…The interlinked negative feedback loops are an example of how the signalosome processes upstream signals. As described below, calcineurin Ab may be an important effector for the mAKAP signalosome (13). We propose that calcineurin Ab is activated by Ca 2þ ions released locally by mAKAPb-associated RyR2.…”
Section: Pka Ryr and Calcineurinmentioning
confidence: 79%
See 4 more Smart Citations
“…The interlinked negative feedback loops are an example of how the signalosome processes upstream signals. As described below, calcineurin Ab may be an important effector for the mAKAP signalosome (13). We propose that calcineurin Ab is activated by Ca 2þ ions released locally by mAKAPb-associated RyR2.…”
Section: Pka Ryr and Calcineurinmentioning
confidence: 79%
“…NFATc translocates into the nucleus when the serine-rich domains are dephosphorylated by calcineurin. We have found that NFATc nuclear translocation in myocytes is reduced when mAKAPb expression is inhibited by RNA interference (13). In addition, NFATc transcriptional reporter activity depends on the presence of the scaffold protein (unpublished observations).…”
Section: Pka Ryr and Calcineurinmentioning
confidence: 81%
See 3 more Smart Citations